Acid-treated high-moisture sorghum for swine - Allee, G.L.; Nelson, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials involving 166 growing pigs (initial weight 20.5 pounds) and 96 finishing pigs (initial weight 108.7 pounds) were conducted to investigate effects of feeding high-moisture, acid-treated sorghum to swine. Sorghum harvested at 23% moisture was treated with 1.2% propionic acid. Method of processing (whole or ground) and method of feeding (complete or free-choice) were also evaluated. Pigs fed high-moisture, acid-treated sorghum in a complete ration gained at the same rate and just as efficiently as pigs fed the dry, complete ration. Feeding of supplement free-choice tended to reduce daily gain but not feed efficiency. Finishing pigs fed whole, high-moisture, acid-treated sorghum required significantly (P<.05) more feed per unit of gain than pigs fed the ground high-moisture, acid-treated sorghum. Acid-treated, high-moisture sorghum in a ground complete ration is equal to dry sorghum in feeding value for swine.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; High-moisture sorghum; Ration; Acid-treated sorghum